2021
DOI: 10.1177/21582440211061334
|View full text |Cite
|
Sign up to set email alerts
|

Level of Income and the Investment Development Path Theory: Evidence From Africa

Abstract: The investment development path theory delineates countries in stages I, II, III, IV, and V according to the level of development as developing, transition, and developed countries. The World Bank’s classification of countries by income, however, identifies countries as lower-income, lower-middle-income, upper-middle-income, and high income. In this paper, we test the investment development path theory for countries based on the level of income using data from 1980 to 2019. Africa offers unique data as it is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…In an earlier study with other colleagues, we found that agricultural FDI explained agricultural GDP (Djokoto et al, 2022). Other studies made similar findings ( (Djokoto, 2013;Gunasekera et al, 2015) whilst the reverse is also true (Djokoto, 2012;Kassem and Awad, 2019;Lv et al, 2010), hence there can be an endogeneity problem.…”
Section: Test For Endogeneitysupporting
confidence: 80%
See 4 more Smart Citations
“…In an earlier study with other colleagues, we found that agricultural FDI explained agricultural GDP (Djokoto et al, 2022). Other studies made similar findings ( (Djokoto, 2013;Gunasekera et al, 2015) whilst the reverse is also true (Djokoto, 2012;Kassem and Awad, 2019;Lv et al, 2010), hence there can be an endogeneity problem.…”
Section: Test For Endogeneitysupporting
confidence: 80%
“…Recently, Djokoto (2021b) found that the IDP explains human development (HD). Further, using the GDP per capita as an indicator for IDP, Djokoto (2022) showed that GDP per capita is positively related to human development. It is worth noting that although GDP per capita is an ingredient in the construction of the HDI, it is not the only ingredient.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations